Development of a paper-based analytical device for colorimetric detection of uric acid using gold nanoparticles–graphene oxide (AuNPs–GO) conjugates. Issue 38 (9th September 2016) - Kumar, Sanjay; Bhushan, Pulak; Bhattacharya, Shantanu
Abstract : A novel paper-based device for colorimetric detection of uric acid was developed based on the peroxidase-like activity of gold nanoparticles–graphene conjugates (AuNPs–GO). Abstract : A novel paper-based device for colorimetric detection of uric acid was developed based on the peroxidase-like activity of gold nanoparticles–graphene conjugates (AuNPs–GO). Theoretical models were utilized for designing a device that was further verified by simulation and experimentation. Detection of uric acid was then carried out by initially soaking the paper in an AuNPs–GO solution and subsequently pipetting TMB–H2 O2 solution on it. Detection was achieved by measuring the color change when uric acid interacted with AuNPs–GO. A significant reduction in the blue coloration of the paper to white color was observed in a brief time of 5 minutes. Moreover, a very low detection limit of 4 ppm for uric acid was obtained on paper by visualization with the naked eye. The assembly of AuNPs within the GO matrix resulted in many active sites, which were the reason for the low detection limit. The practicality of the device was also examined by testing it on several blood serum samples. The results were in agreement with clinical results and also showed a high selectivity towards uric acid. The device provides a real-time, rapid and easy-to-use platform for the detection of uric acid for clinical purposes.